Director Monitoring of Expense Misreporting in Nonprofit Organizations: The Effects of Expense Disclosure Transparency, Donor Evaluation Focus and Organization Performance - Chen, Qiu (Contemporary Accounting Research, 2016)
Abstract This study examines whether three factors—the transparency of expense disclosures, donor evaluation focus, and organization performance—influence how directors monitor management expense misreporting in nonprofit organizations. An experiment with 189 nonprofit directors finds that the enhanced transparency of expense disclosures increases director monitoring by reducing the tendency to accept management expense misreporting. Further, an organization's nonfinancial performance and the perceived fairness of donor evaluation focus interact to influence director monitoring practices. Specifically, when directors know an organization's nonfinancial performance is poor and understand that this performance will negatively influence the willingness of donors to contribute, directors monitor less if they think that donors are adopting a more balanced approach to organizational evaluation that focuses on both financial and nonfinancial performance; that is, there is a reverse fair process effect as this donor approach is perceived as being fairer than if donors focus solely on financial performance. However, monitoring is equally strong regardless of donor evaluation focus when directors know that an organization's nonfinancial performance is good and a donation is forthcoming.